Organisational sources of safety and danger: sociological contributions to the study of adverse events. Issue 2 (1st June 2000) - West, Elizabeth
Abstract : Organisational sociology has long accepted that mistakes of all kinds are a common, even normal, part of work. Medical work may be particularly prone to error because of its complexity and technological sophistication. The results can be tragic for individuals and families. This paper describes four intrinsic characteristics of organisations that are relevant to the level of risk and danger in healthcare settings—namely, the division of labour and "structural secrecy" in complex organisations; the homophily principle and social structural barriers to communication; diffusion of responsibility and the "problem of many hands"; and environmental or other pressures leading to goal displacement when organisations take their "eyes off the ball". The paper argues that each of these four intrinsic characteristics invokes specific mechanisms that increase danger in healthcare organisations but also offer the possibility of devising strategies and behaviours to increase patient safety. Stated as hypotheses, these ideas could be tested empirically, thus adding to the evidence on which the avoidance of adverse events in healthcare settings is based and contributing to the development of theory in this important area. ( Quality in Health Care 2000;9: 120–126)